PENYUSUNAN LAPORAN KEUANGAN MASJID BERDASARKAN PSAK 45 - Fauzi, Mohammad Rizka Cholid; Setyaningsih, Nina Dwi (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2020)
Funds needed by the mosque are mostly obtained from public. The funds obtained can be used and responsibly according their use. More people providing fund to mosque, management must be give a report or financial statement based on financial accounting standard. The purpose of this research is to find out and do the mosque financial report based on PSAK 45, so can give a facility to give an infotmation related mosque finance. This research uses a qualitative approach with descriptive methods. The data obtained in this study came from observations, interviews and documentation The results of this study are the mosque management still has not applied PSAK 45 in the compiling of financial statements.